THE INFLUENCE OF DIABETIC FOOT GYMNASTIC TO BODY BALANCE IN ELDERLY DIABETES MELLITUS PATIENTS IN GATOEL MOJOKERTO HOSPITAL DIABETIC CLUB - Abdul Muhith Muhith; Hannan Mujib Mujib; Dwi Helynarti S; M Himawan S; Ismawati S S; Tatik Sutarti (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2018)
Diabetes mellitus suffers from insulin deficiency which inhibited the transfer of glucose to cells in body tissues that cause starvation cells an in the increase in glucose in the blood that leads to muscle weakness thus disrupt the body’s balance and increase the risk of falling. Diabetic foot exercises aim to improved blood circulation in the feet of people with diabetes mellitus, so that nutrient smoothly to the network. The purpose of this study to determine the effect of diabetic foot gymnastics on body balance elderly people with diabetes mellitus in Diabetic Club Gatoel Hospital Mojokerto in the 27 February – 25 March 2017. This research used a Quasy Experimental method with Pretest-Posttest with Control Group Design. The sampling technique used Simple Random Sampling with the sample of 17 respondents for the control group and 17 respondents for the intervention group. Wilcoxon Signed Rank Test obtained p-value 0,000 < 0,05 concluded that there is an influence of diabetic foot exercises on body balance in elderly people with diabetes mellitus in Diabetic Club Gatoel Hospital Mojokerto. The study recommended that elderly people with diabetes mellitus is expected to take advantage of diabetic foot exercises as an effort to improve the balance of the body to reduce the incidence of fall.